2017
DOI: 10.1021/acsnano.7b07132
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Sulfide Quantum Dot Embedded N/S-Doped Carbon Nanosheets with Superior Reversibility and Rate Capability for Sodium-Ion Batteries

Abstract: Metal sulfides are promising anode materials for sodium-ion batteries due to their large specific capacities. The practical applications of metal sulfides in sodium-ion batteries, however, are still limited due to their large volume expansion, poor cycling stability, and sluggish electrode kinetics. In this work, a two-dimensional heterostructure of CoS (CoS and CoS) quantum dots embedded N/S-doped carbon nanosheets (CoS@NSC) is prepared by a sol-gel method. The CoS quantum dots are in situ formed within ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
223
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(232 citation statements)
references
References 56 publications
4
223
1
Order By: Relevance
“…In the next three sweeps, the broad cathodic peak splits into three peaks around 0.63, 1.33, and 1.65 V, corresponding to the multi‐step electrochemical reactions during lithiation. During the anodic process after the first sweep, the three obvious peaks at 1.35, 2.01, and 2.27 V can be ascribed to the reverse reaction to form the CoS x in the electrode 46. Combined with the relevant literature, the total electrochemical reaction could be described as follows:46, 49 CoSx+2xLinormal++2xnormaleCo+xLinormal2S …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In the next three sweeps, the broad cathodic peak splits into three peaks around 0.63, 1.33, and 1.65 V, corresponding to the multi‐step electrochemical reactions during lithiation. During the anodic process after the first sweep, the three obvious peaks at 1.35, 2.01, and 2.27 V can be ascribed to the reverse reaction to form the CoS x in the electrode 46. Combined with the relevant literature, the total electrochemical reaction could be described as follows:46, 49 CoSx+2xLinormal++2xnormaleCo+xLinormal2S …”
Section: Resultsmentioning
confidence: 96%
“…The other two peaks at 163.8 and 165.1 eV could be identified as C‐S 2p 3/2 and 2p 1/2 , indicating the successful sulfur doping of the carbon. In the case of C (Figure 4d), the peaks centered at 284.7, 286.1, and 288.4 eV can be attributed to C—C, C—S/C—N, and C—N bonds, respectively 46, 48, 50. The presence of C—N bond demonstrates that nitrogen is doped into the carbon lattice.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…These intriguing phenomenon revealed that the reversible SEI films may be formed/ Adv. [73,74] Attracted by the fascinated EIS change, the simplified interfacial models were proposed with the corresponding equivalent circuits, which were used to analyze the variation of the resistance between electrolyte and carbon layer, as well as carbon layer and basic materials. 2019, 9, 1803035 decomposed during cycling, facilitating the improvement of cycling capacity, which have been demonstrated by the previous reports.…”
Section: Exploring the Kinetics And Structure Change Of Ni-pr C-nisementioning
confidence: 99%